2016
DOI: 10.1080/00987913.2016.1207480
|View full text |Cite
|
Sign up to set email alerts
|

Textbooks in Academic Libraries

Abstract: This installment of the Balance Point column delves into the ways in which libraries create and store open educational resources (OER) in institutional repositories (IR), addressing issues such as preservation and versioning of OER content, copyright and licensing, funding, and staffing. Drawing on interviews and the literature, the author highlights programs at institutions such as the University of Minnesota,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These technological advances further enhance attitudes towards ebook use, with usage growing exponentially (Safley, 2006: 456). From the library’s perspective, ebooks provide 24/7 access to information (Ferguson, 2016), underpin distance and part-time learning modes, can meet high demand reading list access (if simultaneous multi-user access is available) (Riha and LeMay, 2016) and save on space compared to multiple print copies (Frederick, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These technological advances further enhance attitudes towards ebook use, with usage growing exponentially (Safley, 2006: 456). From the library’s perspective, ebooks provide 24/7 access to information (Ferguson, 2016), underpin distance and part-time learning modes, can meet high demand reading list access (if simultaneous multi-user access is available) (Riha and LeMay, 2016) and save on space compared to multiple print copies (Frederick, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have felt enjoyment and ease in using e-books [19], [20]. Students choose to use e-books because of their familiarity, usability, utility, and attractiveness; they are very efficient and recommended [21]. The results of the ADDIE development model are as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the academic libraries face the problem of rising cost of printed textbooks. Ferguson 31 identified that acquisition of e-books and e-textbooks is a beneficial solution to the problem of rising cost of printed textbooks. According to Ferguson sharing of e-books across departments is another best way to ensure cost-effective use of e-books.…”
Section: E-books Collection Developmentmentioning
confidence: 99%